Dependence of locked mode behavior on frequency and polarity of a rotating external magnetic perturbation. (27th November 2017) - Inoue, S; Shiraishi, J; Takechi, M; Matsunaga, G; Isayama, A; Hayashi, N; Ide, S
Abstract: Active control and stabilization of locked modes (LM) via rotating external magnetic perturbations are numerically investigated under a realistic low resistivity condition. To explore plasma responses to rotating and/or static external magnetic perturbations, we have developed a resistive magnetohydrodynamic code 'AEOLUS-IT'. By using AEOLUS-IT, dependencies of mode behavior on frequency and polarity of the rotating magnetic perturbation are successfully clarified. Here, the rotational direction of the rotating magnetic perturbation to the equilibrium plasma rotation in the laboratory frame is referred to as 'polarity'. The rotating magnetic perturbation acts on the background rotating plasma in the presence of a static field. Under such circumstances, there exist bifurcated states of the background rotating plasma, which should be taken into account when studying the dependence of the mode behavior on the rotating magnetic perturbation. It is found that there exist an optimum frequency and polarity of the rotating magnetic perturbation to control the LM, and that the LM is effectively stabilized by a co-polarity magnetic perturbation in comparison with a counter-polarity one.